2022
DOI: 10.1002/ijc.34338
|View full text |Cite|
|
Sign up to set email alerts
|

Systemic circulating microRNA landscape in Lynch syndrome

Abstract: Circulating microRNAs (c-miRs) are small noncoding RNA molecules that migrate throughout the body and regulate gene expression. Global c-miR expression patterns (c-miRnomes) change with sporadic carcinogenesis and have predictive potential in early detection of cancers. However, there are no studies that have assessed whether c-miRnomes display similar potential in carriers of inherited pathogenic mismatch-repair gene variants (path_MMR), known as Lynch syndrome (LS), who are predisposed to highly increased ca… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…To separate serum, the whole blood samples were allowed to clot for 30 minutes at room temperature, centrifuged at 1,800 × g for 10 minutes and aliquoted. Methods of sample collection, preanalytic preparation, c-miR extraction, library preparation, and sequencing have been described previously in detail ( 18 ).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…To separate serum, the whole blood samples were allowed to clot for 30 minutes at room temperature, centrifuged at 1,800 × g for 10 minutes and aliquoted. Methods of sample collection, preanalytic preparation, c-miR extraction, library preparation, and sequencing have been described previously in detail ( 18 ).…”
Section: Methodsmentioning
confidence: 99%
“…High-throughput c-miR expression data of cancer-free LS carriers ( n = 86) as well as of healthy non-carrier control samples ( n = 37) were generated as described earlier ( 18 ). Briefly, c-miRs were extracted using affinity column-based approach (miRNeasy Serum/Plasma advanced kit, Qiagen), ligated to sequencing adapters from both 5′ and 3′ end, reverse transcribed into cDNA using unique molecular identifier (UMI)-assigning primers, and purified with magnetic beads (Qiaseq miRNA Library preparation kit, Qiagen).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…73 Nevertheless, certain microRNAs have recently emerged as significant regulators of genes associated with MMR, including MLH1, MSH2, MSH6, and PMS2. 74 Valeri et al identified that mir-155 compromises MMR mission by targeting the 3′UTR of MLH1, MSH2, and MSH6. 75 Overexpression of this molecule correlated with a hypermutated phenotype and MSI in CRC cell lines.…”
Section: Mismatch Repair Machinerymentioning
confidence: 99%